Hank Zaletel letter to Nicholas S. Halmi regarding bird sightings, March 18, 1978 - Zaletel, Hanket al (1978)
Letter from Hank Zaletel regarding bird sightings to Nicholas S. Halmi, March 18, 1978. The observers were Hank Zaletel, Linda Zaletel, and Marilyn Smith Glasson. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed